Friction measurements with yoghurt in a simulated tongue-palate contact. (December 2016) - Tsui, S.; Tandy, J.; Myant, C.; Masen, M.; Cann, P.M.
Abstract: The perception of many food attributes is related to mechanical stimulation and friction experienced in the tongue-palate contact during mastication. Friction in the tongue-palate is determined by the changing film properties (composition, component distribution, thickness) in the conjunction. We suggest this evolution is essentially determined by tongue-palate film loss rather than shear flow entrainment which predominates in conventional bearing lubrication. The paper reports friction measurements in a simulated tongue-palate contact for a range of high and low fat dairy foods. A reciprocating, sliding contact with restricted stroke length (< contact width) was used; under these conditions there is negligible shear-entrainment of fluid from outside the contact area. The tongue-palate contact was simulated by a PDMS ball and glass surface. The effect of hydrophobic and hydrophilic surfaces on friction was investigated for different fat contents (0, 4.2, 9.5% wt fat). Friction was measured over 60 s of rubbing. Significant differences were observed in the friction change with time for different fat contents (μ 9.5 < μ 4.2 < μ 0 wt%) and for different surface energy conditions (μ hydrophilic < μ hydrophobic). Post-test visualisation of the rubbed films showed that low friction coefficient was associated with the formation of a thin oil film on deposited particulate solids. Highlights: Perception of many food attributes (e.g. creaminess) related to friction in the tongue–palate contact during mastication Time-evolution of these properties is determined by food film degradation and loss rather than shear flow entrainment Friction measurements were made in a simulated tongue–palate contact for a range of high and low fat dairy foods. Friction change with time depends on fat content and surface wetting properties of the substrates. Low friction coefficient was associated with the formation of a thin oil film on deposited particulate solids